Enhancing biology learning outcomes through a blended-discovery learning model integrated with the Bioenial website - Opik Prasetyo; Bowo Sugiharto; Harlita Harlita (EDUSAINS, 2026)
The post-COVID-19 shift to blended learning presents a significant challenge for biology education, necessitating innovative pedagogical approaches to adapt to the digital era. This study addresses this need by investigating the effectiveness of a Blended-Discovery Learning (BDL) model, specifically when integrated with the Bioenial website, on students' biology learning outcomes. A quasi-experimental research design with a pretest-posttest non-equivalent control group was employed with 11th-grade students from a private school in Boyolali, Central Java. Three groups were compared: a control class, an experimental class using BDL with Google Classroom, and another experimental class using BDL with the Bioenial website. Data were collected using a multiple-choice test and analysed through ANCOVA. The findings revealed significant improvements in learning outcomes across all groups, as indicated by higher post-test scores compared with pre-test scores. The ANCOVA analysis demonstrated a significant effect of the instructional model on students' biology learning outcomes, with a large effect size (partial η² = 0.343). The BDL model integrated with the Bioenial website yielded the highest learning outcomes, followed by BDL with Google Classroom and the traditional control group. These findings highlight the potential of BDL as an effective instructional strategy in biology education and suggest that integrating BDL with a specialized digital platform can substantially enhance students' learning outcomes. Therefore, the implementation of BDL supported by dedicated web-based learning environments is highly recommended to optimize biology learning in the digital era.